Mechanochemical Signaling of the Extracellular Matrix in Epithelial-Mesenchymal Transition - Scott, Lewis E.; Weinberg, Seth H.; Lemmon, Christopher A. (Frontiers in Cell and Developmental Biology, 2019)
Epithelial-Mesenchymal Transition (EMT) is a critical process in embryonic development in which epithelial cells undergo a transdifferentiation into mesenchymal cells. This process is essential for tissue patterning and organization, and it has also been implicated in a wide array of pathologies. While the intracellular signaling pathways that regulate EMT are well understood, there is increasing evidence that the mechanical properties and composition of the extracellular matrix (ECM) also play a key role in regulating EMT. In turn, EMT drives changes in the mechanics and composition of the ECM, creating a feedback loop that is tightly regulated in healthy tissues, but is often dysregulated in disease. Here we present a review that summarizes our understanding of how ECM mechanics and composition regulate EMT, and how in turn EMT alters ECM mechanics and composition.